Densely Packed Hydrophobic Clustering: Encapsulated Valerates Form a High‐Temperature‐Stable Mo132 Capsule System. (3rd May 2016) - Garai, Somenath; Bögge, Hartmut; Merca, Alice; Petina, Olga A.; Grego, Alina; Gouzerh, Pierre; Haupt, Erhard T. K.; Weinstock, Ira A.; Müller, Achim
Abstract: Porous molecular nanocontainers of Mo132 ‐type Keplerates offer unique opportunities to study a wide variety of relevant phenomena. An impressive example is provided by the highly reactive Mo132 ‐CO3 capsule, the reaction of which with valeric acid results in the very easy release of carbon dioxide and the uptake of 24 valerate ions/ligands that are integrated as a densely packed aggregate, thus indicating the unique possibility of hydrophobic clustering inside the cavity. Two‐dimensional NMR techniques were used to demonstrate the presence of the 24 valerates and the stability of the capsule up to ca. 100 °C. Increasing the number of hydrophobic parts enhances the stability of the whole system. This situation also occurs in biological systems, such as globular proteins or protein pockets.